HAZARDOUS FUME EMISSIONS IN MMA WELDING OF AH-36 STEEL WITH DIFFERENT ELECTRODES AND ANALYSIS WITH TAGUCHI AND ANOVA - Mert, Tolga; Bilgili, Levent; Senoz, Kutsi Mert; Celebi, Ugur Bugra; Ekinci, Serkan (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2017)
Manufacturing sector is crucial for a country's rapid and continuous development and welding is one of the most highly utilized manufacturing processes in heavy industries such as shipbuilding, pipe-line and steel constructions, manufacturing of pressure vessels. Despite many advantages in manufacturing, welding is one of the most important pollution sources and important amount of detrimental fume and noxious gas emissions are emitted during welding. In this study, manual metal arc (MMA) welding of AH-36 structural steel with rutile, basic and cellulosic covered electrodes using variety of parameters were investigated and fume formation rates were measured and analyzed using Taguchi design of experiment method and analysis of variance (ANOVA). In addition, toxic gases formed during welding were measured as well. Results obtained were evaluated in terms of environment friendliness and worker's health.
Keywords: MMA welding; structural steel; fume formation; workers' health; Taguchi; ANOVA; LIFE-CYCLE ASSESSMENT; TECHNOLOGIES; Environmental Sciences & Ecology